Algorithm 822: GIZ, HIZ two Fortran 77 routines for the computation of complex Scorer functions. - Gil, Amparo (ACM transactions on mathematical software.)
Two Fortran 77 routines for the evaluation of Scorer functions of complex arguments Gi(z), Hi(z), and their derivatives are presented. The routines are based on the use of quadrature, Maclaurin series, and asymptotic expansions. For real z, comparison with a previous code by A. J. MacLeod [1994] is provided.